Carotid arteriosclerosis. Diagnosis and treatment - Palma, Eduardo C; Danza, Rómulo (Cirugía del Uruguay, 2020)
A review is made of the various symptoms of carotid stenosis, stress being laid on the variability of the neurologic symptomatology and the importance - because of its frequency - of carotid tenderness at the level of an atheromatous plaque